Topological Quasi-vector Space and It’s Characteristics - Kumar, Nand Kishor; Yadav, Dipendra Prasad (Perspectives on Higher Education, 2024)
This article discusses fundamental concepts and examples related to topological vector spaces. The primary goal of this article is to investigate topological quasi-vector spaces and their properties. This research endeavor begins with the discovery of various features of (topological) quasi-vector spaces that remain invariant under some kind of transformation. Any such transformation should be built in such a way that it can preserve the full quasi-vector spaces - structure. The features of quasi-vector space are used to characterize specific (topological) quasi-vector spaces that play an important role in this article and play a vital function in this research.